2007
DOI: 10.1007/s00423-007-0254-6
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression and apoptosis in liver and spleen during CO2 pneumoperitoneum

Abstract: CO(2) pressure level and application time may affect on cells living in liver and spleen. High pressure and/or long application time may cause releasing of cytokines and superoxide radicals from these organs' cells, and transient or serious organ dysfunctions may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…It is known that apoptosis is a very important contributor in kidney damage during renal I/R injury (25). p53 is a guardian of the genome and DNA damage induces its expression (1). In this study, it was found that there was increase in p53 expression in I/R group, while it was decreased in Dc group showing protective effect of Dc on DNA damage.…”
Section: Discussionsupporting
confidence: 43%
“…It is known that apoptosis is a very important contributor in kidney damage during renal I/R injury (25). p53 is a guardian of the genome and DNA damage induces its expression (1). In this study, it was found that there was increase in p53 expression in I/R group, while it was decreased in Dc group showing protective effect of Dc on DNA damage.…”
Section: Discussionsupporting
confidence: 43%
“…It means that CO 2 pneumoperitoneum in higher pressures have lethal effects on kidney tubular cells. Generally, apoptotic pathways were activated by p53 expression in our before studies [10][11][12][13][14].However, in this study, we detected that p53 expression was detected only 20 mmHg applied groups. This protection might be related with mechanical resistance of renal capsule and also retroperitoneal location of kidneys.…”
Section: Discussioncontrasting
confidence: 82%
“…However, it was revealed that the side effects of CO 2 pneumoperitoneum such as organ ischemia, cell death, physiopathological changes were minimal and reversible without any apparent sequel when the shorter time and lower pressure was used. Because we have studied the effects of CO 2 pneumoperitoneum in different intraabdominal organs in our different studies before [10][11][12][13][14], we have standardized CO 2 pressure for experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] On the other hand, it has been postulated that the use of low pneumoperitoneum pressure (LPP) during laparoscopy could be peritoneum friendly and reduce some of these undesired effects. [17][18][19][20][21] Nevertheless, the impact of lowering intra-abdominal pressure on surgical space conditions and safety has not yet been well established, hence the routine use of this approach still remains controversial. 22 We hypothesized that the use of LPP (8 mm Hg) during laparoscopic cholecystectomy could minimize the adverse impact on the surgical peritoneal environment [measured as gene expression of extracellular matrix adhesion and inflammatory cytokines and apoptotic index (AI)] and improve clinical outcomes.…”
mentioning
confidence: 99%
“…On the other hand, it has been postulated that the use of low pneumoperitoneum pressure (LPP) during laparoscopy could be peritoneum friendly and reduce some of these undesired effects 17–21 . Nevertheless, the impact of lowering intra-abdominal pressure on surgical space conditions and safety has not yet been well established, hence the routine use of this approach still remains controversial 22 .…”
mentioning
confidence: 99%